2017
DOI: 10.1111/modl.12383
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Opportunities to Learn in Teacher Preparation for EFL Teachers’ Pedagogical Content Knowledge

Abstract: The study examines the connection between domain-specific learning opportunities in English as a foreign language (EFL) teacher preparation and preservice EFL teachers' pedagogical content knowledge (PCK). Using a sample of 444 preservice EFL teachers for secondary schools, it contrasts groups at the end of the 2 phases required in German teacher preparation programs: a theoretical phase at university and a supervised professional internship at a school (practical phase). Specifically, it examines differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
3
21
0
2
Order By: Relevance
“…Ayieko (2014) where both dimensions of opportunity to learn were positively related to mathematical belief. Besides that, the findings are also consistent with Konig et al (2017), and Akkoç, and Yesildere (2010) findings which stated that there is a significant relationship between preservice teachers' opportunity to learn through teaching practice (OTL-Practicum) and their pedagogical content knowledge. Furthermore, earlier findings by Toh Tin Lam, Berinderjeet Kaur, and Koay Phong Lee (2009) have established that OTL-Practicum affected Singapore preservice secondary mathematics teachers' content knowledge.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Ayieko (2014) where both dimensions of opportunity to learn were positively related to mathematical belief. Besides that, the findings are also consistent with Konig et al (2017), and Akkoç, and Yesildere (2010) findings which stated that there is a significant relationship between preservice teachers' opportunity to learn through teaching practice (OTL-Practicum) and their pedagogical content knowledge. Furthermore, earlier findings by Toh Tin Lam, Berinderjeet Kaur, and Koay Phong Lee (2009) have established that OTL-Practicum affected Singapore preservice secondary mathematics teachers' content knowledge.…”
Section: Resultssupporting
confidence: 87%
“…Among them are studies by Rachel A. Ayieko (2014) on the teachers from three country found that the opportunity to learn mathematics pedagogy has influence their belief and knowledge. Besides that, the study conducted by Konig et al (2017) on prospective high school English teachers found that OTL content and OTL teaching practices have influenced their pedagogical content knowledge. Regression analysis showed that OTL was able to predict the positive score of the PCK test teacher (β= 0.28 (p<0.01) for OTL content, and (β= 0.29 (p<0.01) for OTL teaching practice (practicum).…”
Section: H1mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, many teacher education programs in Western countries have undergone a paradigm shift, moving away from theory‐driven approaches toward performance‐based assessment (Darling‐Hammond, ). As demonstrated by König et al () and König et al (), theory‐based programs may enrich teachers’ PKB if the construct is measured through paper‐and‐pencil tests; however, they may have little impact on deepening instructors’ practice‐oriented PKB, which is manifested while teachers are engaged in classroom teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Among these elements, the teacher cognition was found to considerably influence decisions related to materials use [30]. However, teacher knowledge for materials use-the crucial concern of materials use research [31]-has only been referenced on a general level [32], rather than being rigorously examined, in foreign language scholarship [33].…”
Section: Materials Use In Language Classroomsmentioning
confidence: 99%